Females are less sensitive than males to the motivational- and dopamine-suppressing effects of kappa opioid receptor activation. (1st March 2019) - Conway, Sineadh M.; Puttick, Daniel; Russell, Shayla; Potter, David; Roitman, Mitchell F.; Chartoff, Elena H.
Abstract: The neuropeptide dynorphin (DYN) activates kappa opioid receptors (KORs) in the brain to produce depressive-like states and decrease motivation. KOR-mediated suppression of dopamine release in the nucleus accumbens (NAc) is considered one underlying mechanism. We previously showed that, regardless of estrous cycle stage, female rats are less sensitive than males to KOR agonist-mediated decreases in motivation to respond for brain stimulation reward, measured with intracranial self-stimulation (ICSS). However, the explicit roles of KORs, circulating gonadal hormones, and their interaction with dopamine signaling in motivated behavior are not known. As such, we measured the effects of the KOR agonist U50, 488 on ICSS stimulation thresholds before and after gonadectomy (or sham surgery). We found that ovariectomized females remained less sensitive than sham or castrated males to KOR-mediated decreases in brain stimulation reward, indicating that circulating gonadal hormones do not play a role. We used qRT-PCR to examine whether sex differences in gene expression in limbic brain regions are associated with behavioral sex differences. We found no sex differences in Pdyn or Oprk1 mRNA in the NAc and ventral tegmental area (VTA), but tyrosine hydroxylase ( Th ) mRNA was significantly higher in female compared to male VTA. To further explore sex-differences in KOR-mediated suppression of dopamine, we used fast scan cyclic voltammetry (FSCV) and demonstrated that U50, 488 was less effective in suppressing evoked NAc dopamine release in females compared to males. These data raise the possibility that females are protected from KOR-mediated decreases in motivation by an increased capacity to produce and release dopamine. Graphical abstract: Image 1 Highlights: Kappa opioid receptor (KOR) activation decreases motivated behavior in ICSS. KOR-mediated decreases in motivated behavior are greater in males than females. Gonadectomy does not change sex differences in KOR effects on motivated behavior. Females have more tyrosine hydroxylase mRNA expression in the VTA than males. KOR activation is less effective at suppressing NAc dopamine release in females.